Anemia pada Ibu Hamil: Tinjauan Status Gizi dan Paritas di Puskesmas Kalibagor - Ikhwah Muminah; khamidah Achyar; Lilik Hartati (INVOLUSI: Jurnal Ilmu Kebidanan, 2026)
Anemia during pregnancy, if left untreated, can lead to serious consequences, including bleeding. Bleeding is the primary cause of the high maternal mortality rate (MMR) in Indonesia, where MMR is an indicator of public health. Government efforts to address MMR in pregnant women have been implemented, including improving the quality of services in health facilities, financing health insurance, direct community outreach efforts by providing at least 90 iron tablets during pregnancy, and providing nutrition education to the community to educate them about nutritious diets, thereby improving the nutritional status of every pregnant woman. Despite various efforts by the government and other stakeholders, anemia during pregnancy remains a health problem in Indonesia. Nutritional status and parity are among the contributing factors to anemia in pregnant women